Organizing Sustainable Development - Aneta Kuźniarska; Karolina Mania; Monika Jedynak (Routledge, 2024)
The role and meaning of sustainable development have been recognized in the scientific literature for decades. However, there has recently been a dynamic increase in interest in the subject, which results in numerous, in-depth scientific research and publications with an interdisciplinary dimension. This edited volume is a compendium of theoretical knowledge on sustainable development. The context analysed in the publication includes a multi-level and multi-aspect analysis starting from the historical and legal conditions, through elements of the macro level and the micro level, inside the organization. Organizing Sustainable Development offers a systematic and comprehensive theoretical analysis of sustainable development supplemented with practical examples, which will allow obtaining comprehensive knowledge about the meaning and its multi-context application in practice. It shows the latest state of knowledge on the topic and will be of interest to students at an advanced level, academics and reflective practitioners in the fields of sustainable development, management studies, organizational studies and corporate social responsibility.
Keywords: 330; CSR; dimensions of sustainable development; innovations; organization; reporting; Sustainable business management; Sustainable Development Goals; Sustainable HRM; Sustainable marketing; Sustainable production; Sustainable servitization; Sustainable supply chains; sustainable development